Teach yourself visually knitting design : - Turner, Sharon (Wiley, 2007)
There are lots of stylish knitting patterns out there, but sometimes you want to do your own thing. Maybe you've found a yarn that would make a beautiful hat, and all you need are basic directions for shaping. Or maybe you've had your eye on a cute sweater in a store window and know that you can make a better version yourself—if you could only figure out the measurements. This handy guide demystifies all that knitting math and shows you how to knit custom-fitted, one-of-a-kind fashions that express your style. Master patterns for hats, sweaters, scarves, shawls, bags, mittens, vests, and socks lay out the basic construction for each item in a range of sizes; you choose the yarn and decide which modifications and customizations you want to make.